Time to consider the risks of caesarean delivery for long term child health. (10th June 2015) - Blustein, Jan; Liu, Jianmeng
Abstract : Jan Blustein and Jianmeng Liu examine the evidence linking caesarean delivery with childhood chronic disease and say that guidelines on delivery should be reviewed with these risks in mind